2022
DOI: 10.1002/smi.3181
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in mental health change during the COVID‐19 pandemic in Germany: The role of social factors

Abstract: The COVID‐19 pandemic constitutes a prolonged global crisis, but its effects on mental health seem inconsistent. This inconsistency highlights the importance of considering the differential impact of the pandemic on individuals. There is some evidence that mental health trajectories are heterogeneous and that both sociodemographic and personal characteristics are associated with higher risk for mental health issues. By contrast, information on the role of social factors as potential determinants of initial rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Three studies found concepts associated with regulatory flexibility [ 75 , 80 , 81 ] to be positively related to resilience trajectories. Similarly, pandemic-related research showed that self-reported resilience was associated with more favorable mental responses for some but not all outcomes [ 52 , 77 , 78 , 89 ]. Optimism was also associated with more favorable mental responses for some outcomes [ 75 , 81 , 82 ].…”
Section: Psychosocial Resilience Factors During Covid-19 Pandemicmentioning
confidence: 99%
“…Three studies found concepts associated with regulatory flexibility [ 75 , 80 , 81 ] to be positively related to resilience trajectories. Similarly, pandemic-related research showed that self-reported resilience was associated with more favorable mental responses for some but not all outcomes [ 52 , 77 , 78 , 89 ]. Optimism was also associated with more favorable mental responses for some outcomes [ 75 , 81 , 82 ].…”
Section: Psychosocial Resilience Factors During Covid-19 Pandemicmentioning
confidence: 99%
“…An identified limitation of previous studies investigating the mental health impact of the pandemic is their focus on overall “mean effects without addressing the possibility of heterogeneity in mental health” response (p.2) ( 38 ). However, in this study we sought to examine contributing factors to mental distress in order to identify sub-groups of individuals most at risk and in need of support.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a change in the emotional representation of the disease. Initial increase in negative emotions [23,31] was followed with a slight decrease in the negative perceptions of COVID-19 [4], and even with a sense of positive changes in life [32]. However, a meta-analysis [33] of research reports focusing on mental health during the COVID-19 pandemic showed that stress and mental burden in this case were comparable to war time experiences.…”
mentioning
confidence: 93%
“…Healthcare workers and elderly people were commonly perceived as a high-risk group, as opposed to children or young people. As for the consequences of COVID-19, numerous studies clearly showed that the pandemic was perceived as a factor adversely affecting mental health, social functioning, or economic status [3][4][20][21][22][23] and leading to existential crisis [24]. Researchers have also shown links between representation of COVID-19 and individual factors.…”
mentioning
confidence: 99%